Scheimpflug and Optical Coherence Tomography Analysis of Posterior Keratoconus. Issue 10 (October 2016) - Abdala-Figuerola, Alexandra; Navas, Alejandro; Ramirez-Miranda, Arturo; Lichtinger, Alejandro; Hernandez-Bogantes, Erick; Olivo-Payne, Andrew; Cabral-Macias, Jesus; Graue-Hernández, Enrique O.
Abstract : Purpose: To report a case series of 7 eyes of 6 patients with posterior keratoconus, evaluating corneal Scheimpflug tomographic changes and anterior-segment optical coherence tomography (OCT). Methods: In our descriptive study, 6 patients were diagnosed with posterior keratoconus: 5 unilateral (7-, 33-, and 42-year-old males and 64- and 60-year-old female) and 1 bilateral (45-year-old female). Patients were diagnosed with slit-lamp examination, which revealed corneal opacity with an underlying posterior corneal depression. Additional analysis with anterior-segment OCT and Scheimpflug tomography evaluation was performed. Results: Localized paracentral posterior keratoconus was diagnosed in 7 eyes. Scheimpflug images demonstrated posterior corneal depression. Clinical findings were examined by OCT. Genetic analysis revealed no alterations or associated syndromes. All patients were amblyopic in the affected eye, and no surgery was offered to improve their visual acuity. Conclusions: Posterior keratoconus is a rare noninflammatory condition usually present at birth and sometimes related to developmental abnormalities. Posterior keratoconus is usually unilateral and can present as a generalized or localized change in posterior corneal curvature.